PW 2659 Trend analysis for assessing remaining at-risk activities and environmental factors as toddler immersion mortality approaches target zero, canada 1991–2014. (November 2018) - Barss, Peter; Olsen, Karlyn; Tehami, Yasmina; Hamilton, Jane; Dalke, Shelley
Abstract : Background: Toddler (ages 1–4) immersions appear a 1990s success story for Canadian drowning prevention. We reassess methods to indicate paths towards target zero. Objective: To assess use of trends in activities and risk factors to study a category by age of high mortality reduction – in the interest of targeting remaining mortality. Methods: The first national injury surveillance in Canada began in 1991, for water-related injury, and is now at the quarter century mark. Immersion data have been collected prospectively from coroners during 1991–2014. Incidence trends and evolving activities and risk factors among 1–4 year-olds were assessed by R and Excel. Trends were assessed by negative binomial modelling. Results: There were 643 immersion deaths of toddlers. Total incidence reduction was −88% (p 0.000), IRR (incidence rate ratio) 0.94, 95% CI 0.92, 0.95 (Z=7.86, p=0.000) Average annual percent change −6.3%. Incidence fell from 2.98/100, 000/year during 1991–95 to 2.21 in 1996–2000, to 1.45 in 2001–05, slowing to 1.06 in 2006–10, and edging up to 1.23 in 2011–14. Most immersions involved non-aquatic activity with falls into water while playing near water. Although a major reduction occurred, falls have remained the leading factor. Incidence began high in lakes and home pools and still remains highest there despite major improvements. Large reductions in immersions of indigenous peoples occurred. Sustained major rate reduction took place in the three largest provinces, while remaining high in the Prairies. Many toddlers drown alone or under care of other children. As toddlers age from 1 to 4 years, death increasingly results during delegation to other children. Conclusions: Falls into water, pools, lakes and adult bathtubs should be targets. Increasing use of child caregivers as toddlers age suggest needs for subsidised community daycare, and barriers for play-area pools, or homes near water. Toddler drownings are unacceptable – target zero is within reach.